Feasibility of a short message service (SMS) intervention to deliver tuberculosis testing results in peri-urban and rural Uganda. (August 2019) - Babirye, Diana; Shete, Priya B.; Farr, Katherine; Nalugwa, Talemwa; Ojok, Christopher; Nantale, Mariam; Oyuku, Denis; Ayakaka, Irene; Katamba, Achilles; Davis, J. Lucian; Nadunga, Diana; Joloba, Moses; et al.
Abstract: Background: Pre-treatment loss to follow-up is common for patients diagnosed with tuberculosis (TB) in high-burden countries. Delivering test results by Short-Messaging-Service (SMS) is increasingly being considered as a solution, but there is limited information about its feasibility as a public health tool in low resourced settings. Objective: We sought to assess the feasibility of utilizing SMS technology to deliver TB test results during routine TB diagnostic evaluation in Uganda. Methods: We conducted a single arm interventional pilot study at four community health centers in Uganda that referred sputum samples to a district hospital for GeneXpert-MTB/RIF (Xpert) testing (Cepheid, USA). Using existing GxAlert-software (SystemOne, USA), we set up an automated SMS platform to send Xpert results to patients and referring health centers. We assessed each step of the SMS delivery cascade for consecutive patients who presented to these four community health centers between December 2015 and March 2016 and underwent Xpert testing. Results: Of 233 patients enrolled, 161 (69%) had phone numbers recorded on individual Xpert referral forms. Phone numbers were entered into Xpert device software in the correct format for 152 (94%) patients. GxAlert-software generated an automated SMS reporting Xpert results for 151 (99%) patients and delivered it successfully to mobile phone service providers for 145/151 (96%). Of the 123 patients reached by phone to determine receipt of test results, 114 (93%) confirmed SMS receipt. SMS-based delivery of Xpert results was verified for 114/233 (49%) patients overall. In contrast, phone calls to health centers confirmed that health centers received messages for 222/233 (95%) patients. Conclusion: Reporting Xpert results via automated SMS is technically feasible and results in approximately half of patients receiving their test results immediately. Additional research should be done to address process inefficiencies in order to maximize impact of this technology and link its successful utilization to improved patient outcomes.